2005
DOI: 10.1042/bj20041829
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental oxidation of thiol–disulphide redox couples during epidermal growth factor signalling

Abstract: Exogenously added ROS (reactive oxygen species) cause generalized oxidation of cellular components, whereas endogenously generated ROS induced by physiological stimuli activate discrete signal transduction pathways. Compartmentation is an important aspect of such pathways, but little is known about its role in redox signalling. We measured the redox states of cytosolic and nuclear Trx1 (thioredoxin-1) and mitochondrial Trx2 (thioredoxin-2) using redox Western blot methodologies during endogenous ROS production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
157
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(166 citation statements)
references
References 32 publications
9
157
0
Order By: Relevance
“…With some oxidants (e.g. epidermal growth factor-induced ROS) (Halvey et al, 2005;Hansen et al, 2006a), Trx2 is not significantly oxidized. The reason(s) for the enhanced sensitivity of Trx2 to Cr(VI) are not known, but could indicate a more robust interaction of Cr(VI) with the mitochondrial thioredoxin system or a lesser ability of the mitochondrial system to restore or maintain Trx2 in its reduced state once it has been oxidized.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With some oxidants (e.g. epidermal growth factor-induced ROS) (Halvey et al, 2005;Hansen et al, 2006a), Trx2 is not significantly oxidized. The reason(s) for the enhanced sensitivity of Trx2 to Cr(VI) are not known, but could indicate a more robust interaction of Cr(VI) with the mitochondrial thioredoxin system or a lesser ability of the mitochondrial system to restore or maintain Trx2 in its reduced state once it has been oxidized.…”
Section: Discussionmentioning
confidence: 99%
“…The redox states of Trx1 and Trx2 have been used to differentially assess the impacts of other oxidants on the thiol redox status of the cytosolic and mitochondrial compartments (Halvey et al, 2005;Hansen et al, 2006a). For the studies reported here, both insoluble and soluble Cr (VI) cause a dose-and time-dependent oxidation of Trx1 and Trx2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations